Protein induced by vitamin K absence or antagonist II (PIVKA‐II) producing large cell neuroendocrine carcinoma (LCNEC) of lung with multiple liver metastases: A case report. Issue 2 (11th January 2017) - Kurohama, Hirokazu; Mihara, Yumi; Izumi, Yasumori; Kamata, Masatsugu; Nagashima, Seiji; Komori, Atsumasa; Matsuoka, Yojiro; Ueki, Nozomi; Nakashima, Masahiro; Ito, Masahiro
Abstract : A 78‐year‐old man was admitted to our hospital for multiple lung and liver tumors. Initial clinical diagnosis was hepatocellular carcinoma (HCC) with lung metastases because of a high value of serum protein induced by vitamin K absence or antagonist II (PIVKA‐II) (6, 705 mAU/mL). However, a review of a prior CT showed the lung tumor had existed 6 months before liver tumors were detected. The tumors progressed rapidly and the patient died 37 days after admission. Autopsy revealed that both lung and liver tumors exhibited the histology of large cell neuroendocrine carcinoma (LCNEC). Immunohistochemistry revealed that the tumor cells expressed not only neuroendocrine markers but also PIVKA‐II diffusely. Hepatoid differentiation was not detected. Background liver did not show any chronic liver disease. The final diagnosis was PIVKA‐II producing LCNEC of the lung with multiple liver metastases. PIVKA‐II producing tumors other than HCC are extremely rare. To our best knowledge, this is the first case report of PIVKA‐II producing neuroendocrine tumors of the lung.